STUDY ON THE DYNAMIC CHARACTERISTICS OF THE MAIN DRIVE SYSTEM OF ROLLING MILL - GUO ZhiQiang; CHANG MingRui; REN XuePing; YANG Jie (Jixie qiangdu)
The gap can result in the characteristics of the main drive system of the mill become bad,the influence of the gap size on the system is the concern of enterprises. This paper is based on numerical simulation and finite element analysis,to study the main drive system of the initial mill with multiple gaps,its dynamic characteristics are changed due to the difference of gap size. a The difference of dynamic response and stress change of the system is obtained by using MATLAB numerical simulation and ANSYS finite element calculation. This two methods verify and supplement each other to provide theoretical reference for mill production practice.